Head impulse testing in bilateral vestibulopathy in patients with genetically defined CANVAS. Issue 6 (2nd May 2022) - Borsche, Max; Tadic, Vera; König, Inke R.; Lohmann, Katja; Helmchen, Christoph; Brüggemann, Norbert
Abstract: Background: To investigate the association between disease duration and the severity of bilateral vestibulopathy in individuals with complete or incomplete CANVAS (Cerebellar Ataxia with Neuropathy and Vestibular Areflexia Syndrome) and biallelic RFC1 repeat expansions. Methods: Retrospective analysis of clinical data and the vestibulo‐ocular reflex quantified by the video head impulse test in 20 patients with confirmed biallelic RFC1 repeat expansions. Results: Vestibulo‐ocular reflex gain at first admittance 6.9 ± 5.0 years after disease onset was 0.16 [0.15–0.31] (median [interquartile range]). Cross‐sectional analysis revealed that gain reduction was associated with disease duration. Follow‐up measurements were available for ten individuals: eight of them exhibited a progressive decrease of the vestibulo‐ocular reflex gain over time. At the first visit, six of all patients (30%) did not show clinical signs of cerebellar ataxia. Conclusions: Our data suggest a pathological horizontal head impulse test, which can easily be obtained in many outpatient clinics, as a sign of bilateral vestibulopathy in genetically confirmed CANVAS that can precede clinically accessible cerebellar ataxia at least in a subset of patients. The presumably continuous decline over time possibly reflects the neurodegenerative character of the disease. Thus, genetic testing for RFC1 mutations in (isolated) bilateral vestibulopathy might allow disease detection before the onset of cerebellar signs. Further studies including a wider spectrum of vestibular function tests are warranted in a prospective design. Abstract : To investigate the association between bilateral vestibulopathy and disease duration in genetically defined CANVAS, the vestibulo‐ocular reflex was quantified by the video head impulse test in 20 RFC1 repeat expansion carriers. We found a decrease in vestibulo‐ocular reflex gain over time, possibly reflecting the neurodegenerative character of the disease. Furthermore, our data suggest that bilateral vestibulopathy might precede cerebellar ataxia in RFC1‐associated disease, at least in a subset of patients.